Will to Power, Nietzsche’s Last Idol - Joullié, Jean-Etienne. author. aut Link
XII, 242 p.
Keywords: The book proposes a critique of Nietzsche's works 'from within'. In doing so, it answers the continuing question asked by any reader of Nietzsche: Why did he decide not to write the major work he said he would write?